ANALISIS KEBIJAKAN PELAKSANAAN PERATURAN MENTERI PENDIDIKAN NASIONAL NOMOR 70 TAHUN 2009 TENTANG PENDIDIKAN INKLUSIF DI PROVINSI ACEH - Harri Santoso; Teuku Haflisyah; Andy Chandra; Noor Aini Ahmad (Majelis Pendidikan Aceh, 2021)
Inclusive Education is education that provides opportunities for students with disabilities to attend public schools. This study aims to look at the extent of the policies contained in the Minister of National Education Regulation No. 70 of 2009 concerning the implementation of inclusive education in Indonesia carried out in Aceh province. Aceh provinces through Aceh Governor’s Regulation number 92 of 2012 concerning the administration of inclusive education require education providers in Aceh to accommodate students with disabilities to study in public schools. The study was conducted on training participants conducted by the Ministry of Education and Culture of the Republic of Indonesia in collaboration with the Pionir Nusantara Foundation on the Teaching Model for children with disabilities in December 2019. Participants are shadow teachers who work in each District/City implementing inclusive education in Aceh, including: Banda Aceh, Aceh Besar, Bireun, Pidie and Pidie Jaya as many as 25 person. Data collection techniques through Focus Group Discussion on 7 aspects of implementation in the Regulation of the Minister of National Education Number 70 Year 2009, namely: Receiving student with disabilities according to needs and abilities, Availability of at least 1 Inclusive School for each level in each sub-district, Availability of shadow teacher, Support from the government and various parties, Guidance and Supervision, Awards and sanctions. The results showed that the implementation of inclusive education in 5 cities in Aceh was still not running optimally with a variety of challenges both from the government, the community and the school itself. The researcher suggests the need for an inclusive education working group at every level, both provincial and district/city, to provide guidance and supervision on the implementation of inclusive education in each district/city.